HBV vaccination status among healthcare workers: A cross-sectional study. Issue 1 (January 2020) - Garzillo, Elpidio Maria; Arnese, Antonio; Coppola, Nicola; Corvino, AnnaRita; Feola, Daniela; Monaco, Maria Grazia Lourdes; Signoriello, Giuseppe; Marsella, Luigi Tonino; Arena, Paola; Lamberti, Monica
Objective: The development of a vaccine against hepatitis B virus (HBV) is one of the improvements in strategy prevention during the last decades. Aim: To evaluate HBV-related vaccine status in healthcare workers (HCW) exposed to biological risk. Methods: The serum markers for HBV were collected from HCWs in two tertiary care hospitals in Naples (Italy). Multivariate statistical analysis was then performed to identify associated factors linked to the long-term immunogenicity of the HCWs. Results: All HBV vaccinated individuals were screened for whole marker patterns; all were HBsAg/anti-HBc negative. Of individuals, 20% had an anti-HB antibody titre < 10 IU/L. Multivariate statistical analysis highlighted that women were more protected than men (73.6% vs. 26.4%, P < 0.05). Additionally, nurses seem to maintain a higher antibody titre than doctors and other staff, such as auxiliary technicians ( P < 0.05). Conclusions: Our data support the evidence of a strong immunogenicity against HBV, assessed through the circulating antibody titre, when prophylactic vaccination is conducted in non-infantile age, particularly for women. The outcome of the study supports the central role of occupational physicians within the hospital districts in terms of primary prevention and maximum protection of HCWs.